Analysis and 3D Imaging of Morphometric-Mineral Structure Changes in Skulls of Male and Female Guinea Pigs During and After Developmental Period - Baygeldi, Saime Betül; Yilmaz, Yücehan; Güzel, Barıs Can; Kanmaz, Yesim Aslan; Karan, Meryem; Hark, Betül Dagoglu; Yilmaz, Sadik (Universidad de la Frontera, 2024)
Even though morphometric and mineral studies related to the guinea pig (Cavia porcellus) skull have been carried out, this study is the first attempt to evaluate all developmental stages of male and female guinea pigs. This study aims to this study is to create 3D modeling of CT images obtained from the skulls of male and female guinea pigs during the developmental period (prepuberty and the period between puberty and adulthood) and following periods (young adulthood and old adulthood), to analyze some biometric bone data such as volume, surface area and length, and to assess the developmental analysis of the mineral matter change in their skulls. The CT-scanned skulls were transferred to 3D Slicer (5.0.2), which is used for 3D modeling. The surface area and volume were calculated by measuring the measurement points on the models. In addition, the XRF device was used to show elemental ratio changes during different developmental stages. According to metric measurements, a gradual increase was observed during the life period. The metric measurements of the skull bone had a higher measurement value in male guinea pigs than in their female counterparts. While Ca/P ratio increased up to the third group and partially decreased in the fourth group in males, it gradually increased from the first group to the fourth group in females. This study revealed that puberty, adulthood and sex were effective in the physical and chemical characterization of skull bone structure in guinea pigs. © 2024, Universidad de la Frontera. All rights reserved.
Análisis e Imágenes 3D de Cambios Morfométricos y de Estructura Mineral en Cráneos de Cobayas Machos y Hembras Durante y Después del Período de Desarrollo
Keywords: 3D; Cavia porcellus; Guinea pig; Morphometry; Skull; XRF